2022
DOI: 10.1242/dev.200074
|View full text |Cite
|
Sign up to set email alerts
|

TAF4b transcription networks regulating early oocyte differentiation

Abstract: Establishment of a healthy ovarian reserve is contingent upon numerous regulatory pathways during embryogenesis. Previously, mice lacking TBP-associated factor 4b (Taf4b) were shown to exhibit a diminished ovarian reserve. However, potential oocyte-intrinsic functions of TAF4b have not been examined. Here we use a combination of gene expression profiling and chromatin mapping to characterize TAF4b-dependent gene regulatory networks in mouse oocytes. We find that Taf4b-deficient oocytes display inappropriate ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…Distinctive GO categories from the CUT&RUN included RNA processing, chromatin modification, and cell cycle regulation. The most consistent DNA motifs within the TAF4b-bound promoters included Sp/Klf family and NFY binding sites; a remarkable similarity to our findings in embryonic mouse oocytes, and for the first time linking these ubiquitous factors to the regulation of ProSpg transcription [24]. Finally, we compared our male embryonic germ cell data with our recently reported TAF4b genomic analyses of female embryonic germ cells revealing several core and sex-specific cellular processes regulated by TAF4b.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…Distinctive GO categories from the CUT&RUN included RNA processing, chromatin modification, and cell cycle regulation. The most consistent DNA motifs within the TAF4b-bound promoters included Sp/Klf family and NFY binding sites; a remarkable similarity to our findings in embryonic mouse oocytes, and for the first time linking these ubiquitous factors to the regulation of ProSpg transcription [24]. Finally, we compared our male embryonic germ cell data with our recently reported TAF4b genomic analyses of female embryonic germ cells revealing several core and sex-specific cellular processes regulated by TAF4b.…”
Section: Introductionsupporting
confidence: 71%
“…Our work indicates that TAF4b performs essential developmental functions in spermatogenesis and oogenesis. We thus compared our findings in E16.5 male ProSpg (from this study) to E16.5 oocytes [24]. We plotted all our samples in one PCA plot and observed that the samples separated Accordingly, we conclude from all of these data that TAF4b regulates both sex-independent and sex-dependent embryonic germ cell development further highlighting its critical transcription functions regulating male and female mammalian fertility.…”
Section: Integrating E165 Prospg and Oocyte Genomic Data Reveals Sex-...mentioning
confidence: 74%
See 3 more Smart Citations